Research on Dynamic Mechanism and Management Mode of Sports Tourism Development in China - Fang Fang Hu, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Sports tourism can stimulate the development of related industries, such as tourism, recreation, service, business industry, retail industry and so on. Therefore, it has been attracting attention from all over the world. With the Beijing Olympic Games, Guangzhou Asian Games and Shanghai World Expo held one after another, China has paid some attention to the development of Sports tourism. International convention and exhibition centers have been built in Shanghai, Shenzhen, and other first-tier cities in China, and activities are carried out regularly to attract domestic and foreign tourists. sports tourism has become a hot topic in domestic tourism development, but due to the late start of China's sports industry, relevant research is also lagging behind. In order to better develop China's Sports tourism, it is necessary to draw on the advanced experience of foreign countries in developing Sports tourism, construct a Sports tourism business model with Chinese characteristics and establish an MICE tourism business system in line with China's national conditions. Therefore, the core idea of this paper is to build a user-oriented personalized tourism information recommendation model on the existing big data of Sports tourism, combine data mining knowledge and recommendation system algorithm, and analyze the development power mechanism and management mode of Sports tourism. The research concludes that Sports tourism should be closely integrated with Sports industry, give full play to its industry advantages to serve Sports industry, promote Sports tourism at a deeper level and form an interactive win-win effect.